(untitled) (jornal of the libyan geographical society, 1996)
Applied geography is one of the modern trends in geographical research, and it is defined as: the application of geographical techniques and methods to contemporary problems. Since geography, as a science, is concerned with studying natural and human phenomena and their spatial relationships, a study based on interpretation, analysis, connection and evaluation, education, as a phenomenon, is part of the geography of services that has grown greatly after the great development that has occurred in the study of urban geography. With its school community, to which a large segment of the population belongs, and with its educational facilities that constitute a prominent feature of the urban landscape and matters related to the distribution of those facilities, all of this represents raw material for geographical research. The geographer Raymond Murphy pointed to this phenomenon, and identified the areas in which geographical research can contribute in the field of education. He also predicted that geographical studies would increase as long as education in cities expands and spreads.